Pengaruh Penambahan Limbah Marmer terhadap Campuran AC-WC dengan Asbuton LGA 50/30 - Wahid, Muhammad Shidiq Abdu Rahman; Pristyawati, Tantin; Ristanto, Iwan (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
The AC-WC asphalt layer is the layer that has the smoothest structure compared to other layers. The presence of a tightly graded mixture that has few voids in the AC-WC asphalt mixture causes this layer to be sensitive to variations and mixture proportions. This research uses innovative marble waste materials with the aim of analyzing the effect of adding Asbuton LGA 50/30 to AC-WCs with marble waste. The method used is experimentation with Marshall characteristic parameters. The research results of 5 variations of marble waste mixtures were used with variation values ​​of 15%, 20%, 25%, 30% and 35%. For asbuton with a 9% VIM value, there are 4 variants that do not meet Bina Marga specifications, namely 15%, 25%, 30% and 35%. Meanwhile, 12% asbuton is found in the Flow value in the 15% and 20% variants. The highest stability variation value of 9% asbuton was found in a mixture of 35% marble waste with a stability value of 1817.22kg, with a VIM value of 3.20%, a VMA value of 16.18%, a VFA value of 85.17%, a flow value of 3.95 mm , and the MQ value is 684.24 kg/mm. The 12% abuton variation content has the highest stability value found in the 15% marble variation with the highest stability value of 1856.30kg, VIM value of 4.11%, VMA value of 15.700%, VFA value of 75.326%, flow value of 3.80 mm, and MQ value 632.86kg/mm. These two variants were declared the most effective for AC-WC asphalt mixtures because their Marshall values ​​are in accordance with the 2018 Bina Marga specifications